Protocol for a study of the psychosocial determinants of health in early childhood among children with cystic fibrosis. (10th February 2015) - Douglas, Tonia; Jordan, Brigid; Priddis, Lynn; Anderson, Vicki; Sheehan, Jane; Kane, Robert T.; Massie, John; Branch‐Smith, Cindy; Shields, Linda; AREST‐CF
Abstract Aims To investigate the causal associations between family relationships, family functioning, social circumstances and health outcomes in young children with cystic fibrosis. Background The anticipated health gains for patients with cystic fibrosis, promised by early diagnosis through newborn screening, have yet to be fully realized, despite advances in cystic fibrosis health care with aggressive management in multidisciplinary clinics and the development of specific medications. Adverse psychosocial functioning may underpin the current lack of progress as it is well recognized that compromised early parent–child attachment relationship experiences and adverse social circumstances have negative impacts on lifelong health status and health resource use, even in healthy children. Design A cross‐sectional (initial) and longitudinal (progressive), multicentre study of children aged 3 months–6 years with cystic fibrosis, who have been diagnosed by newborn screening. Methods Questionnaire and observational measures of parent psychosocial functioning, parenting and parent–child attachment and social markers; and including clinical outcomes of regular health surveillance with clinical, lung imaging (computerized tomography) and bronchoalveolar lavage for airway microbiology and inflammation. Conclusion This will be the first study to investigate the causal effect of psychosocial functioning, parenting and attachment on physical health outcome measures in children with cystic fibrosis.